'URF: APPLICATION HALAL ANIMAL SLAUGHTER PRACTICE - Ma’mun Nawawi; Hadi Peristiwo (Universitas Mathla’ul Anwar Banten, 2022)
Islamic law receive development and vulnerable to changes, especially about certain legal issues that need to be clarified based upon particular needs and circumstances of the time. The practice of slaughtering animals that have been changed from the conventional method to be a technique that is more modern in which the method of slaughter by using the machine and method of slaughter others have been used to accommodate requests and ensure the quality of meat that is halal and thayib . However, these modern practices have raised concerns in terms of its legal decisions, because the issue is not discussed and decided in the classical manual of Islamic law 'Urf is one of the legal methods used to obtain legal decisions relating to certain legal issues, is flexible because it reflects the circumstances and practices of people in one place and a certain time. This study uses a qualitative approach. The method used in this research is descriptive analysis. Sources of data in this study came from books, journals and interviews with informants related to 'urf as a method of Islamic law in implementing the practice of halal animal slaughter. From the results of the study can be obtained conclusion thats one of the methods that can be used to determine the legal status of Islam associated with the process of halal animal slaughter, especially on the final result of halal meat products is ' urf. 'Urf is considered an appropriate method of Islamic law and is related to halal slaughter of animals, as far as animal slaughter is concerned it will involve changes in the methods that have been used.